Analysis of the Implementation of Performance-Based Budgeting at the State Christian Institute (IAKN) Kupang - Devi, Ni Putu Jayanti Kusuma; Rozari, Petrus De; Mas’amah, Mas’amah (PT Keberlanjutan Strategis Indonesia, 2026)
This study examines the implementation of performance-based budgeting at the State Christian Institute (IAKN) Kupang in response to increasing demands for transparency and accountability in public financial management, particularly in religious higher education institutions. Although budget realization at IAKN Kupang is relatively high, the achievement of performance indicators remains suboptimal, indicating a gap between budget absorption and organizational outcomes. This study aims to analyze the extent of performance-based budgeting implementation and to identify the factors that support and hinder its effectiveness. A qualitative approach was employed, with data collected through interviews, documentation, and observation, and analyzed using Miles and Huberman’s interactive model. The findings indicate that performance-based budgeting has been implemented through participatory (bottom-up) planning and the use of digital systems. However, the implementation still emphasizes administrative compliance rather than outcome achievement. Supporting factors include leadership commitment, regulatory support, and the role of internal quality assurance units. In contrast, inhibiting factors consist of delays in fund disbursement, limited human resource competencies, weak coordination between units, the absence of Standard Operating Procedures and Key Performance Indicators, and difficulties in measuring non-physical program outcomes. Overall, the implementation of performance-based budgeting at IAKN Kupang remains in a transitional stage toward a results-oriented budgeting system, requiring improvements in capacity building, performance measurement, coordination, and fund disbursement mechanisms.